Shear strain sampling points of plate element from desirable displacement fields and mixed finite elements - Vimonsatit, Vanissorn; Kowsuwan, Teerapon (ISEC Press, 2015)
A newly developed four-node bilinear plate element based on linked interpolation and Desirable Displacement Field (DDF) concept is formulated for the analysis of general plate problems. The proposed element is formulated on a mixed finite element for Reissner-mindlin plate theory and transverse displacement is linked to the rotation degree of freedom to ensure high-order interpolation capacity. By assumed strain method, the DDF is introduced for the investigation of strain sampling points. A high order polynomial for transverse displacement with linking shape function is used in finite element discretization to provide a better solution for the plate problems. A number of commonly selected problems will be tested using the present element to compare with other element models in the open literature to assess their relative convergence and accuracy.